2000
DOI: 10.1007/pl00010654
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal EPR studies of the oxidized active site of [NiFe] hydrogenase from Desulfovibrio vulgaris Miyazaki F

Abstract: The Ni-A and the Ni-B forms of the [NiFe] hydrogenase from Desulfovibrio vulgaris Miyazaki F have been studied in single crystals by continuous wave and pulsed EPR spectroscopy at different temperatures (280 K, 80 K, and 10 K). For the first time, the orientation of the g-tensor axes with respect to the recently published atomic structure of the active site at 1.8 A resolution was elucidated for Ni-A and Ni-B. The determined g-tensors have a similar orientation. The configuration of the electronic ground state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 33 publications
9
68
0
Order By: Relevance
“…The relatively low S character (ca. 3±4 %) derived from the bridging thiolate S donors in the SOMO of 1 À contrasts with the electronic structures of the Ni-A, [20,22] -B, [20,22] -C [18,21,22] and -L [18,21,22] forms of the [NiFe] hydrogenases derived from single-crystal EPR studies supported by DFT calculations. These studies reveal the majority of the spin density is oriented along the NiÀ S(Cys533) bond and only a small amount is at the low-spin formally Fe II centre in the Ni-A, Ni-B and Ni-C forms of the enzyme.…”
Section: Modelmentioning
confidence: 71%
“…The relatively low S character (ca. 3±4 %) derived from the bridging thiolate S donors in the SOMO of 1 À contrasts with the electronic structures of the Ni-A, [20,22] -B, [20,22] -C [18,21,22] and -L [18,21,22] forms of the [NiFe] hydrogenases derived from single-crystal EPR studies supported by DFT calculations. These studies reveal the majority of the spin density is oriented along the NiÀ S(Cys533) bond and only a small amount is at the low-spin formally Fe II centre in the Ni-A, Ni-B and Ni-C forms of the enzyme.…”
Section: Modelmentioning
confidence: 71%
“…The smallest experimental g value is close to the free electron value g e , indicating a d z 2 ground state. In the crystal studies, the g z -axis is found to be approximately oriented along the Ni-SCys533 bond [51]. This is also the direction of the empty free coordination position at the Ni (Fig.…”
Section: The Oxidized States Ni-a and Ni-bmentioning
confidence: 92%
“…Additionally, we also compared the calculated g tensor orientation with that obtained from angular-dependent EPR experiments on protein single crystals [50,51]. The smallest experimental g value is close to the free electron value g e , indicating a d z 2 ground state.…”
Section: The Oxidized States Ni-a and Ni-bmentioning
confidence: 94%
See 2 more Smart Citations